Inconsistencies in Modeling the Efficacy of the Oncolytic Virus HSV1716 Reveal Potential Predictive Biomarkers for Tolerability - Howard, Faith; Conner, Joe; Danson, Sarah; Muthana, Munitta (Frontiers in Molecular Biosciences, 2022)
Intralesional HSV1716 treatment has proven successful for melanoma patients with the hope, oncolytic virotherapy would become another weapon in the systemic anticancer therapy (SACT) arsenal. Besides challenges surrounding the systemic delivery of oncolytic viruses (OVs), problems associated with its in vivo modelling has resulted in low predictive power, contributing to the disappointing clinical efficacy seen. As OV’s efficacy is elicited through interaction with the immune system, syngeneic orthotopic mouse models offer the opportunity to study these with high reproducibility and lower cost however, inbred animals display specific immune characteristics which may confound results. Systemic delivery of HSV1716 was therefore assessed in multiple murine models of breast cancer. Viral tolerability was strain dependent with C57/Bl6 the most tolerant and Balb/c experiencing lethal side effects when delivered intravenously. Maximum tolerated doses were not enough to demonstrate efficacy against tumour growth rates or survival of Balb/c and FVB mousel models therefore the most susceptible strain (Balb/c mice) were treated with immunomodulators prior to virus administration in an attempt to reduce side effects. These studies demonstrate the variables to consider when modeling efficacy of OVs and the complexities involved in their interpretation for translational purposes. By reporting these observations we have potentially revealed a role for T cell helper polarization in viral tolerability. Importantly, these findings translated to human studies whereby a Th1 cytokine profile was expressed in pleural effusions of patients that responded to HSV1716 treatment for malignant pleural mesothelioma with minimal side effects, warranting further investigation as a biomarker for predictive response.